SOCIAL CAPITAL OF FISHERMAN COMMUNITIES IN KAMPUNG NELAYAN SEBERANG BELAWANIOF NORTH SUMATERA PROVINCE - Nia Astari; Firman Nugroho; Viktor Amrifo (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research is about social capital of fisherman communities in Kampung Nelayan Seberang Belawan Iof North Sumatera Provincehas been done in Apri-Mey 2018. The purpose of this research is to find out social capital structures, functions of social capital, and mechanisms of social capital maintenance of fisherman communities in Kampung Nelayan Seberang. The research method used is Case Study Method by researching the status of research subjects. The sampling technique used is the snowball sampling technique that is initially small and then enlarged with the number of informants that are not determined and stopped after the research informations isconsidered already enough. The results showed that are five types of capital, natural capital, human capital, physical capital, financial capital and social capital. Social capital has an important role in bonding relations between fishermen, without of social capital, other capital cannot be accessed because social capital is the capital whitchmoving other capital. The social capital structure, has a participation in a networks, resiprocitys, trusts, norms, values, and proactive actions in good condition. Such functions of social capital solve problems, unite and build participations. Maintenance of social capital by uniting social solidarity, making rules, balance and proactive actions.Keywords: Social Capital, Communities Fisherman, Fisherman Village.